Analysis of Student Perception on Teacher-Student Interpersonal Relationship in Chemistry Teaching - Maulidina, Dessy; Agung, Salamah; Yunita, Luki (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The aims of this study are to analyze the interpersonal relationships between chemistry teachers and their students, to investigate chemistry teacher interpersonal behaviour using Model for Interpersonal Teacher Behaviour (MITB), and to identify the interpersonal behaviour profile of chemistry teacher according to student’s perception. The data were collected from 472 eleventh grade students of science class in 5 Public Senior High School and 5 Private Senior High School in South Tangerang Municipality who were randomly sampled using teacher-student interpersonal relationships questionnaire adapted from Questionnaire on Teacher Interaction (QTI). Data were analyzed using Rasch model in Winsteps version 3.73. Results showed that in general, it was indicated that the interpersonal relationships of chemistry teachers and their students are categorized as relatively good. The teachers were considered to have adequately dominant and very cooperative behaviour with students in classroom. Meanwhile, in terms of interpersonal behaviour scale, students perceived their teachers as having higher rate on leadership, helping/friendly, and understanding behaviour than the hostility behaviour. Then, according to interpersonal behaviour profile, it showed that chemistry teachers in South Tangerang Municipality were identified as authoritative.